Evaluation of pharmaceutical and microbial qualities of some herbal medicinal products in South Western Nigeria (2007)
Purpose: The aim of the present study was to investigate the pharmaceutical and microbial qualities of 21 different (of various dosage forms) Herbal Medicinal Products (HMPs) sourced from some traditional medicine sales outlets and retail pharmacy outlets in south western Nigeria. Method: The pharmaceutical qualities evaluated include tablet crushing strength, friability, disintegration time; density of the solutions and suspensions; particle size and angle of repose of the powders. Phytochemical tests were carried out to assess the class of compounds present in the formulations and the microbial quality of the products was also evaluated. Results: The results show that twelve (57.1 %) of the products had their manufacturing and expiry dates stated, nine (42.9%) products have been registered by NAFDAC and ten (47.6%) did not have their content stated but had their therapeutic claims indicated on the container. The tablet formulation (Product A) showed acceptable crushing strength and friability but failed the test for disintegration time. The angle of repose of the powder dosage forms were considerably high showing that the powders were highly cohesive and not free flowing. The microbial load of the products varied considerably. Ten (47.6%) of the samples were contaminated by E. coli, seven (33%) were contaminated by Salmonella, fifteen (71.4%) were contaminated by Staphylococcus aureus and twelve (57.1%) were contaminated by fungi. Conclusion: There is need for constant monitoring and control of the standards of herbal medicines available in the Nigerian market.